(untitled) (Research, Society and Development, 2021)
The Ocotea puberula (Rich.) Nees (Lauraceae) (popular name is canela-guaiacá) is rich in secondary metabolites, among them, the alkaloids. Dicentrine is an alkaloid from O.puberula and have pharmacological actions such as anti-inflammatory, analgesic, anxiolytic and antimalarial. The objective of this work was to investigate the antioxidant and biological potential of the alkaloid dicentrine isolated from the galls of Ocotea puberula. To evaluate the antioxidant potential, the techniques of the formation of the phosphomolybdenum complex, Prussian blue and the reduction of DPPH• were used and the biological activity was evaluated using Artemia salina, sheep erythrocytes, Aedes aegypti larvae and two target species. The phosphomolybdenum method showed an antioxidant potential of 90.68% compared to rutin, 30.88% compared to BHT and 16.62% compared to ascorbic acid. By the DPPH• method it presented IC50 = 943.11 µg.mL-1, indicating low antioxidant potential. When evaluating dicentrine in Artemia salina, a low toxic potential and a non-hemolytic effect were verified in sheep erythrocytes. In the larvicidal activity in Aedes aegypti, dicentrin showed LC50 = 23.62 µg.mL-1. On Lactuca sativa, dicentrine did not influence germination, IVG and hypocotyl growth, but root growth was stimulated with 250 µg.mL-1 and inhibited with 500 µg.mL-1. On Allium cepa dicentrine with 25 and 100 µg.mL-1 stimulated the germination percentage and the GVI. The growth of the Allium cepa root was not influenced, however, the coleoptile was stimulated with 25 µg.mL-1 and inhibited with 50 µg.mL-1. After evaluating the results presented in the chosen tests, it was observed that dicentrine has a larvicidal and allelopathic potential.